Associations between community water fluoridation cessation and the prevalence of dental caries and fluorosis in Alrass city, Saudi Arabia - Alrashdi, Murad (Frontiers in Oral Health, 2025)
BackgroundThe relationships between fluoride exposure, dental caries, and fluorosis are well-known, but the long-term effects of changes in community water fluoridation practices remain unclear, particularly in Alrass city, Saudi Arabia.AimThis study investigated how community water fluoridation cessation affected the prevalence of dental caries and fluorosis in Alrass City, Saudi Arabia.DesignThis retrospective cross-sectional study included 568 participants aged 6–50 years, who were recruited through stratified random sampling in schools and public places. Clinical examinations were conducted using the DMFT index for caries and Dean's Fluorosis Index for fluorosis. Data analysis was performed to compare the difference in caries and fluorosis between age groups and between current and historical data across age groups.ResultsResults showed significantly higher DMFT scores in adults (5.62) compared to children (3.98) (p < 0.0001). Dental fluorosis prevalence was higher in adults (41%) than children (18%) (p < 0.0001). Compared to historical data, mean DMFT scores significantly increased in both groups, while fluorosis prevalence decreased (p < 0.001). Subgroup analysis revealed lower DMFT scores in ages 6–12 compared to 19–50. Multivariate regression confirmed age as a significant predictor of DMFT scores (p < 0.001). Overall, caries prevalence increased and fluorosis decreased post-cessation of well water usage.ConclusionThese findings underscore the dual-edged nature of fluoride exposure through community water supply systems.